An overview: Current progress on hydrogen fuel cell vehicles. (5th February 2023) - Aminudin, M.A.; Kamarudin, S.K.; Lim, B.H.; Majilan, E.H.; Masdar, M.S.; Shaari, N.
Abstract: The harmful consequences of pollutants emitted by conventional fuel cars have prompted vehicle manufacturers to shift towards alternative energy sources. Currently, fuel cells (FCs) are commonly regarded as highly efficient and non-polluting power sources capable of delivering far greater energy densities and energy efficiency than conventional technologies. Proton exchange membrane fuel cells (PEMFC) are viewed as promising in transportation sectors because of their ability to start at cold temperatures and minimal emissions. PEMFC is an electrochemical device that converts hydrogen and oxidants into electricity, water, and heat at various temperatures. The pros and cons of the technology are discussed in this article. Various fuel cell types and their applications in the portable, automobile, and stationary sectors are discussed. Additionally, recent issues associated with existing fuel cell technology in the automobile sector are reviewed. Highlights: PEMFCs are promising in transportation sectors with minimal emissions. This study reviews the pros and cons of this technology. It also discuss the various type of fuel cells and their applications. Recent issues associated with existing fuel cell technology in the automobile sector are aslo reviewed.